A framework for semantic publishing of modular content objects - David, Catalin; Ginev, Deyan; Kohlhase, Michael; Matican, Bogdan; et al. (1st Workshop on Semantic Publishing 2011, SePublica 2011 - Co-located with the 8th Extended Semantic Web Conference, ESWC 2011, 2011)

An architecture for linguistic and semantic analysis on the ARXMLIV corpus - Ginev, Deyan; Jucovschi, Constantin; Anca, Stefan; Grigore, Mihai; David, Catalin; Kohlhase, Michael (39th Jahrestagung der Gesellschaft fur Informatik e.V. (GI): Im Focus das Leben, INFORMATIK 2009 39th Annual Meeting of the German Informatics Society (GI): Focus on Life, INFORMATIK 2009, 2009)

MathML-aware article conversion from LATEX a comparison study - Stamerjohanns, Heinrich; Ginev, Deyan; David, Catalin; Misev, Dimitar; Kohlhase, Michael; et al. (2nd Workshop on Towards a Digital Mathematics Library, DML 2009, 2009)

Scientific statement classification over arXiv.org - Ginev, Deyan; Miller, Bruce (LREC 2020 Conference Proceedings, 2020)
We introduce a new classification task for scientific statements and release a large-scale dataset for supervised learning. Our resource is derived from a machine-readable representation of the arXiv.org collection of preprint articles. We explore fifty author-annotated categories and empirically motivate a task design of grouping 10.5 million annotated paragraphs into thirteen classes. We demonstrate that the task setup aligns with known success rates from the state of the art, peaking at a 0.91 F1-score via a BiLSTM encoder-decoder model. Additionally, we introduce a lexeme serialization for mathematical formulas, and observe that context-aware models could improve when also trained on the symbolic modality. Finally, we discuss the limitations of both data and task design, and outline potential directions towards increasingly complex models of scientific discourse, beyond isolated statements.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Large corpora; Math-rich natural language processing; Statement classification task

The LaTeXML daemon: Editable math on the collaborative web - Ginev, Deyan; Stamerjohanns, Heinrich; Kohlhase, Michael; Miller, Bruce (Symposium on Learning, Knowledge, and Adaptivity 2011, LWA 2011, 2011)

The planetary system: Executable science, technology, engineering and math papers - Lange-Bever, Christoph; Kohlhase, Michael; David, Catalin; Ginev, Deyan; Kohlhase, Andrea; Matican, Bogdan; Zholudev, Vyacheslav; et al. (8th Extended Semantic Web Conference, ESWC 2011, 2011)

The planetary system: Web 3.0 & active documents for STEM - Kohlhase, Michael; Corneli, Joe; David, Catalin; Ginev, Deyan; Jucovschi, Constantin; Kohlhase, Andrea; Lange-Bever, Christoph; Matican, Bogdan; Zholudev, Vyacheslav; et al. (11th International Conference on Computational Science, ICCS 2011, 2011)
In this paper we present the Active Documents Paradigm (semantically annotated documents associated with a content commons that holds the corresponding background ontologies) and the Planetary system (as an active document player). We show that the current Planetary system gives a solid foundation and can be extended modularly to address most of the criteria of the Executable Papers Challenge.
Keywords: Active documents; Content commons; Executable paper challenge; Ontologies; Semantic annotation

The SMGloM project and system: Towards a terminology and ontology for mathematics - Ginev, Deyan; Jucovschi, Constantin; Kohlhase, Andrea; Kohlhase, Michael; Wiesing, Tom; et al. (Springer Verlag, 2016)

Transforming large collections of scientific publications to XML - Stamerjohanns, Heinrich; Kohlhase, Michael; Ginev, Deyan; David, Catalin; Miller, Bruce (Mathematics in Computer Science, 2010)